SOI Design Analog, Memory and Digital Techniques - Marshall, Andrew; Natarajan, Sreedhar (Springer US, 2002)
Silicon on insulator (SOI) is a very attractive technology for large volume integrated circuit production and is particularly good for low-voltage, low-power and high-speed digital systems. SOI has also proved to be effective in various niche and growing markets. IC processes based on SOI are known to reduce susceptibility to radiation, and have been used for many years in high radiation environments. SOI is also used for power integrated circuits, micro-electromechanical systems (MEMS), integrated optics and high temperature applications. SOI offers numerous opportunities and challenges in the design of low-voltage and low-power CMOS circuits for both analog and digital applications. The benefits of this technology for digital applications have been clear for many years.